Online Dynamic Replication and Placement Algorithms for Cost Optimization of Online Social Networks in Two-tier Multi-cloud - Ali Y. Aldailamy; Abdullah Muhammed; Rohaya Latip; Nor Asilah Wati Abdul Hamid; Waidah Ismail (Elsevier, 2024)
Indexed by WOS/Scopus/ERA